The Effect of Environmental Comfort and Quality of Doctor's Examinations on Outpatient Satisfaction at Mentari 2 Clinic Bandung Regency - Nurhadiyansah Nurhadiyansah; A. Rohendi; Rinawati Rinawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to find out how the picture of environmental comfort, the quality of doctor's examinations, and outpatient satisfaction, as well as to find out how the effect of environmental comfort and the quality of doctor's examinations on outpatient satisfaction at Mentari 2 Clinic Bandung Regency. The factors tested in this study were the comfort of the environment and the quality of the doctor's examination as independent variables. Meanwhile, outpatient satisfaction is a dependent variable. The research method used in this study is a verification method. The population in this study is outpatients of Mentari 2 Clinic in Bandung Regency which totals 13,843. The sample determination technique used in this study is the probability sampling technique with a simple random sampling method, and uses the yamane formula with a significance level of 10%, so that the sample in the study is 96 outpatients. The analysis method used in this study is multiple linear regression analysis at a significance level of 10%. Based on the results of the partial and simultaneous study, it shows that the comfort of the environment and the quality of doctor's examinations have a significant effect on the satisfaction of outpatients at the Mentari 2 Clinic in Bandung Regency. In addition, the magnitude of the influence of environmental comfort and the quality of doctor's examinations in contributing to outpatient satisfaction was 62.8%.